Associations of Benzodiazepine With Adverse Prognosis in Heart Failure Patients With Insomnia. Issue 7 (9th April 2020) - Sato, Yu; Yoshihisa, Akiomi; Hotsuki, Yu; Watanabe, Koichiro; Kimishima, Yusuke; Kiko, Takatoyo; Kanno, Yuki; Yokokawa, Tetsuro; Abe, Satoshi; Misaka, Tomofumi; Sato, Takamasa; Oikawa, Masayoshi; et al.
Abstract : Background: The prognostic impact of benzodiazepines has been unclear in patients with heart failure (HF). Methods and Results: This was a historical observational cohort study. A total of 826 patients who had been hospitalized for HF and were being treated for insomnia with either benzodiazepines or Z‐drugs (zolpidem, zopiclone, or eszopiclone), were enrolled and divided on the basis of their hypnotics: benzodiazepine group (n=488 [59.1%]) and Z group (n=338 [40.9%]). We compared the patient characteristics and postdischarge prognosis between the groups. The primary end points were rehospitalization for HF and cardiac death. The benzodiazepine group was older (age, 72.0 versus 69.0 years; P =0.010), had a higher prevalence of depression (17.4% versus 8.9%; P <0.001), and showed a higher use of loop diuretics (77.9% versus 67.8%; P =0.001). In the laboratory data, the benzodiazepine group demonstrated lower levels of hemoglobin (12.3 versus 13.0 g/dL; P =0.001), sodium (139.0 versus 140.0 mEq/L; P =0.018), and albumin (3.7 versus 3.9 g/dL; P =0.003). Kaplan‐Meier analysis showed that both end points were higher in the benzodiazepine group (rehospitalization for HF, log‐rank P =0.001; cardiac death, log‐rank P =0.043). Multiple Cox proportional hazard analysis revealed that the use of benzodiazepines was an independent predictor of rehospitalization for HF (hazard ratio, 1.530; 95% CI, 1.025–2.284; P =0.038). Furthermore, rehospitalization for HF was higher in the benzodiazepine group after propensity score matching (log‐rank P =0.036). Conclusions: Benzodiazepine is associated with higher risk of rehospitalization for HF compared with Z‐drugs in patients with HF.